Review of number of antenatal care admission in antenatal care ward in tertiary care center - Jadhao, Ruchita; Palve, Tushar; Bulchandani, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: This is systematic review to identify and analyse the main factors affecting the antenatal care (ANC) admission in ANC ward. The main objective to study the ANC admission in hospital for women with different age group, gestational age, gravida status, pregnancy complications in terms of maternal and perinatal outcomes and to explore the factors contributing to the alarming situation. Methods: Total 50 women of reproductive age group admitted in ANC ward in the Department of Obstetrics and Gynecology, CAMA and ALBESS Hospital, Mumbai, Maharashtra, India from a period of January to December 2021. Results: The 50 women of reproductive age group admitted in ANC ward. Most of the subjects belong to age 21-25 is 16 (32%), most of primigravida were 29 (58%), according to gestational age, most of the patient belong 2nd trimester, approx. The 22 patient (44%), followed by 3rd trimester, approx. 21 (42%) and least are belong from 1st trimester are 7 (14%). Most of patients presented with vomiting, 9 out of 50 (18%), followed by pain in abdomen 8 out of 50 (16%). Out of total 50 patient, 44 patient are doing fine and stable, 2 patients are delivered. Two patients in bad condition are transferred to ICU department. Conclusions: There is need of proper ANC and need of intensive monitoring of mother throughout hospitalization to prevent complication related to maternal and foetal outcome.